PERAN ARSITEK DALAM FENOMENA PEMBANGUNAN PERKOTAAN - Yohana Nursruwening (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2010)
Abstract            The land of Indonesia basically consists of many layers. The land of Indonesia physically experiences changes because of the improvement in society activity that is called development.Architects have big role in the change of the land of Indonesia through their design such as the developed and built environment, and the City Government involves inside as the authority holder element and the policy maker in the city development.The source of the development success lies on the creative efforts from the architects who give contribution in the discovery of new facts and new expressions for the development. Development brings improvement which influences a lot to the ideas of the task giver side.The continuity of the development planning which is acceptable in the eyes of society will be guaranteed.The key words: City Development, The Role of Architects, and Built Environment.